2017
DOI: 10.1128/aem.00165-17
|View full text |Cite
|
Sign up to set email alerts
|

Erratum for Algburi et al., Control of Biofilm Formation: Antibiotics and Beyond

Abstract: Page 5, lines 2-4: "QS compounds include N-acyl-homoserine lactones (AHLs), produced by Gramnegative bacteria, and autoinducing peptides (autoinducer 2 [AI-2]) produced by Gram-positive bacteria" should read "QS compounds include N-acyl homoserine lactones (AHLs) (produced by Gram-negative bacteria), autoinducing peptides (produced by Gram-positive bacteria), and autoinducer 2 (AI-2) (produced by Gram-positive and Gram-negative bacteria)."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…However, heavy metals and large amounts of proteases are not suitable for the control of biofilms formed on meat. Other studies have applied glycosidases, proteases and DNases to and their combinations to degrade the extracellular matrix 64 . The effectiveness of these enzymes can depend on environmental conditions and their effect on meat is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, heavy metals and large amounts of proteases are not suitable for the control of biofilms formed on meat. Other studies have applied glycosidases, proteases and DNases to and their combinations to degrade the extracellular matrix 64 . The effectiveness of these enzymes can depend on environmental conditions and their effect on meat is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The latter mainly includes a range of substances such as polysaccharides, proteins, nucleic acids, and lipids, forming a dense physical barrier that renders, along with other mechanisms, biofilm cells much more resistant to antibacterial drugs than their non-adherent planktonic cells 8 , 9 . In recent years, much attention has been directed to uncovering new approaches including combination therapy against biofilm infections 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Control of bacterial biofilm formation is considered as one major strategy against bacterial infections, and thus efforts have been made to identify effective inhibitors that go beyond conventional antibiotics for their ability to disrupt biofilm formation 10 . For example, it has been reported that three chemical substances, zinc lactate, stannous fluoride and furanone, and two antibiotics, azithromycin and rifampicin, can inhibit bacterial biofilm formation, but cannot effectively control the infection caused by biofilm-forming bacteria 12 17 .…”
Section: Introductionmentioning
confidence: 99%
“…By adapting themselves with these challenges, the bacterial species often acquire resistance against the conventional drugs. [38] Thus, it's a tough challenge to the scientific community to overcome the chronic bacterial infections threat concerning biofilm, posed by the bacteria and to search alternative treatments, which can eradicate biofilm efficiently. P. aeruginosa is a well-known gram-negative bacteria causing 70 to 80 % nosocomial infections in patients, suffering from cystic fibrosis, urinary tract infections, upper respiratory tract infection, and patients with organ transplants.…”
Section: Introductionmentioning
confidence: 99%